ANALISIS STUDI LITERATUR ATAS PRAKTIK PENGGELAPAN PAJAK PADA KASUS YANG TERJADI DI INDONESIA - Nathalie, Carina Irene; Setiawan, Temy (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
Abstrak The purpose of this research is to (1) Find out what factors influence taxpayers actions in commiting tax evasion; (2) Know what theories are used in tax evasion research. This research used a qualitative descriptive method with 87 Sinta articles for the 2018-2023 period with the keyword “Tax Evasion”, with 8 respondents and an interview with one of the sources as a tool to confirm these factors. The results of this research show that the main factors of tax evasion are Tax Discrimination, Love of Money, Understanding of Taxation, and Opportunity. Meanwhile, the theories that are ofted used are Theory Planned Behaviour and Attribution Theory.